Recent Applications of α-Carbonyl Sulfoxonium Ylides in Rhodium- and Iridium-Catalyzed C–H Functionalizations - Wu, Xiaopeng; Sun, Song; Yu, Jin-Tao; Cheng, Jiang (Synlett, 2019)
Sulfoxonium ylides are a special type of sulfur ylides that serve as new C1 or C2 synthons recently developed for use in C–H functionalization to access acylmethylated or cyclized compounds through the formation of metal carbene species. Many excellent works have reported the syntheses of various useful skeletons from these versatile synthons. These developments have not previously been completely investigated or reviewed. In this review, we summarize recent advances in the use of α-carbonyl sulfoxonium ylides in C–H functionalizations, including ortho-C–H acylmethylation reactions and ortho-C–H activation/cyclization reactions.Table of Contents1 Introduction2 Ortho-C–H Acylmethylation Reactions3 Ortho-C–H Activation/Cyclization Reactions3.1 Ortho-C–H Activation/Cyclization of Anilines and Enamines3.2 Ortho-C–H Activation/Cyclization of Azobenzenes3.3 Ortho-C–H Activation/Cyclization of N-Methoxybenzamide3.4 Ortho-C–H Activation/Cyclization of Imines3.5 Ortho-C–H Activation/Cyclization of N-Azoloimines3.6 Ortho-C–H Activation/Cyclization of Benzoylacetonitriles3.7 Ortho-C–H Activation/Cyclization of Benzoyl Sulfoxonium Ylides4 Conclusion
Keywords: sulfur ylides; C–H functionalization; acylmethylation; cyclization; metal carbenes